Akara Laundromat / Alia Bee Aziz Khan ... [et al.] - Aziz Khan, Alia Bee; Mohd Zain, Aqilah Zaiyanie Said; Perman, Azwan Ahzran; Mogindol, Kimberly Jacqueline; Amsir, Redhayyana (2011)
In the dawn of the new era, more families have both parents working as opposed to the past where one would stay at home while the other would work. There's a new social phenomena, which is the dominance of two-income families, which thus leads the families to prefer a more convenient form of services such as self-service laundry which is also known as Laundromat. This service has the potential to grow in popularity as the working individuals have less time to do household chores and laundry. Therefore, the timing is right to commence this new venture due to the increasing demand of laundry service. Besides, it was the ambition of the founders to one day start together their own laundry business, and with the knowledge to support the venture, has made it as business opportunity with huge potential. Why do we choose this business? Firstly, based on a survey from the Coin Laundry Association (2008), people nowadays have their own washers and dryers at home, but for the sake of convenience they prefer to use self service laundry. This is because with the regular capacity washer machine at home, it takes quite a lot of time to do lot of laundry. That is why we choose to put forward self service laundry. A person just has to run over to the shop, use a couple of the large washer machines and get their laundry done in just less than an hour.